Store-operated calcium entry in disease: Beyond STIM/Orai expression levels. (October 2019) - Kappel, Sven; Borgström, Anna; Stokłosa, Paulina; Dörr, Kathrin; Peinelt, Christine
Abstract: Precise intracellular calcium signaling is crucial to numerous cellular functions. In non-excitable cells, store-operated calcium entry (SOCE) is a key step in the generation of intracellular calcium signals. Tight regulation of SOCE is important, and dysregulation is involved in several pathophysiological cellular malfunctions. The current underlying SOCE, calcium release-activated calcium current (ICRAC ), was first discovered almost three decades ago. Since its discovery, the molecular components of ICRAC, Orai1 and stromal interaction molecule 1 (STIM1), have been extensively investigated. Several regulatory mechanisms and proteins contribute to alterations in SOCE and cellular malfunctions in cancer, immune and neurodegenerative diseases, inflammation, and neuronal disorders. This review summarizes these regulatory mechanisms, including glycosylation, pH sensing, and the regulatory proteins golli, α-SNAP, SARAF, ORMDL3, CRACR2A, and TRPM4 channels.